The heterogeneous microstructure of heat affect zone and its effect on creep resistance for friction stir joints on 9Cr–1.5 W heat resistant steel. (1st January 2019) - Zhang, Chao; Cui, Lei; Wang, Dongpo; Liu, Yongchang; Liu, Chenxi; Li, Huijun
Abstract: The heterogeneity of microstructures in heat affect zone of 9Cr-1.5 W heat resistant steel friction stir welding joint was studied, and its influence on the weld creep property was discussed. The inter critical heat affect zone at the advancing side of the weld is found as the most likely area to be failure during creep, owing to the formation of ferrite grains and lath martensite with low carbon content and the coarsening of M23 C6 carbides. The as-welded joint exhibits a good creep resistance of 1173.8 h creep rupture time at 600 °C temperature and 200 MPa stress. Graphical abstract: Unlabelled Image